Potensi Pengembangan Usahatani Integrasi Tanaman Sereh Wangi Menjadi Minyak Atsiri dan Ternak Sapi di Kabupaten Ogan Ilir - Henny Malini; Eka Mulyana; Friska Syaiful (Seminar Nasional Lahan Suboptimal, 2021)
Malini H,  Mulyana E, Syaiful F.  2021. Potential for farming development integration of citronella plants into essential oils and cattle in Ogan Ilir District. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 648-659. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Farming System Development Integration of Citronella and cattle not only contributes to the development of agriculture and animal husbandry, but also improves the community's economy. This study aims to analyze the potential for developing an integrated farming model of Citronella into essential oils and cattle, by looking at Internal and External factors in Ogan Ilir Regency. The method used in this research is the Case Study method, the data processing method used is EFE and IFE analysis. This analysis is a systematic identification of various factors in order to maximize strengths and opportunities but simultaneously minimize weaknesses and threats. The score obtained from the matrix (IFE) is 3.50 and the score (EFE) is 3.153, thus what is the position of the business in cell 1 of the Internal External (IE) matrix which means Growth and build. The suggested strategy under these conditions is an intensive strategy (market penetration, market development and product development).